Odpowiedź:
[tex]\frac{3}{8} / (-2,5) = \frac{3}{8} / (-\frac{5}{2}) = \frac{3}{8} * (-\frac{2}{5}) = -\frac{6}{40}[/tex]
[tex]\frac{7}{4} / 2,5 = \frac{7}{4} / \frac{9}{2} = \frac{7}{4} * \frac{2}{9} = \frac{14}{36} = \frac{7}{18}[/tex]
[tex]\frac{3}{4} / 2,5 = \frac{3}{4} / \frac{5}{2} = \frac{3}{4} * \frac{2}{5} = \frac{6}{20}[/tex]
[tex]\frac{11}{8} / 2,5 = \frac{11}{8} / \frac{5}{2} = \frac{11}{8} * \frac{2}{5} = \frac{22}{40}[/tex]
[tex]\frac{7}{2} / 1,5 = \frac{7}{2} / \frac{3}{2} = \frac{7}{2} * \frac{2}{3} = \frac{14}{6} =2\frac{2}{6} = 2\frac{1}{3}[/tex]